Functional outcome after arthroscopic debridement with microfracture and platelet rich-plasma injection in osteoarthritis of knee - A prospective study - Sandesh Agarawal; Prabhu Ethiraj; Arun Heddur Shanthappa; Sachin C Thagadur (Wolters Kluwer Medknow Publications, 2022)
Surgical treatment for knee osteoarthritis (OA) involves debridement, lavage, and microfracture to enhance chondral resurfacing by providing a suitable environment for tissue regeneration. Platelet-rich plasma (PRP) stimulates chondrocyte proliferation. Combining microfracture with PRP injections helps promote early clinical improvement, and this study aims to assess the functional outcomes when all three techniques are used simultaneously. This prospective, observational, hospital-based study was conducted at R. L. Jalappa Hospital and Research Centre, SDUMC, Tamaka, involving patients with OA of the knee from June 2020 to November 2020. Clinical data were collected and evaluated with pre -and post-procedure Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and visual analogue scale (VAS) scores. In all, 74.29% of the patients had Kellgren-Lawrence grade III knee OA and 25.71% had grade II knee OA. The levels of pain and knee function were evaluated using WOMAC and VAS scores before and 1, 3, and 6 months after the procedure. It was observed that 68.57% had good VAS scores, while 31.43% had poor scores. The mean WOMAC scores showed a statistically significant improvement (P < 0.001) with a decrease in the preoperative WOMAC score from 67.11 ± 8.73 to 50.14 ± 9.99 at 1 month, 40.83 ± 7.8 at 3 months, and 31.66 ± 5.28 at 6 months. Intra-articular PRP injection after debridement and microfracture is beneficial for pain relief and functional improvement and prolongs the treatment efficacy of microfracture in patients with symptomatic knee OA.